COVD-26. TELEPHONE CONSULTATIONS IN NEURO-ONCOLOGY DURING THE COVID-19 PANDEMIC: LEVELS OF PATIENT SATISFACTION AND COMPARISON WITH TRADITIONAL FACE-TO-FACE CONSULTATIONS. (9th November 2020) - Toman, Emma; Goddard, Claire; Berki, Frederick; Garratt, William; Scott, Teresa; Sher, Zenab; Stevens, Andrew; Petrik, Vladimir; Ughratdar, Ismail; White, Anwen; Zisakis, Athanasios; Watts, Colin; et al.
Abstract: INTRODUCTION: Controversy exists as to whether telephone clinics are appropriate in neurosurgical-oncology. The COVID-19 pandemic forced neuro-oncology services worldwide to re-design and at the University Hospitals Birmingham UK, telephone clinics were quickly implemented in select patients to limit numbers of patients attending hospital. It was important to determine how these changes were perceived by patients. METHODS: A 20-question patient satisfaction questionnaire was distributed to patients who attended neuro-oncology clinic in person ("face-to-face"), or via the telephone. Fisher's exact test was used to determine significance, which was set at p< 0.05. RESULTS: Eighty questionnaires were distributed between June 2020 and August 2020. Overall, 50% (n=40) of patients returned the questionnaire, 50% (n=23) of face-to-face and 50% (n=17) telephone patients. Of those who received telephone consultations, 88% (n=15) felt the consultation was convenient, 88% (n=15) were satisfied with their consultation and 18% (n=3) felt they would have preferred to have a face-to-face appointment. Of those who attended clinic in person, 96% (n=22) felt their consultation was convenient, 100% (n=23) were satisfied with their consultation and 13% (n=3) would have preferred a telephone consultation. Within the face-to-face clinic attendees, only 13% (n=3) were concerned regarding the COVID risk associated with attending hospital. There was no significant difference in patient convenience or satisfaction (p=0.565 and p=0.174 respectively) between face-to-face and telephone clinics. There was no significant difference in whether patients would've preferred the alternative method of consultation (p > 0.999). CONCLUSION: Our study suggests that careful patient selection for neuro-oncology telephone clinic is not inferior to face-to-face clinic. Telephone clinic during COVID-19 pandemic proved to be convenient, safe and effective. This global health crisis has transformed telephone neuro-oncology consultations from an experimental innovation into established practice and should be continued beyond the pandemic in select cases.